CENTRAL NERVOUS SYSTEM NEOPLASMS IDENTIFICATION IN BASRAH - Shaker Khsheesh Al-maliki, Hisham; Faiq Abood Al-Khalidy, Khalid; Fadel Alashoor, Maithem (International Journal of Psychosocial Rehabilitation, 2022)
The brain, meninges, and spinal cord compose the central nervous system and are made up of specialized neuron cells. They are sites for the transmission and storage of information. When exposed to any lesions lead to a significant proportion of mortality and morbidity. Those lesions are anatomical lesions and severely affect the inner body systems and their function and most of the patients were unaware until the stages progress and may become fatal. The present study aimed to determine the central nervous system neoplasms in Basrah. Retrospectively collected data of 92 cases proved to have brain tumors by histopathological examination from private, inpatients, and outpatients clinics during five years. Both sexes enrolled (56 males and 36 females), and their ages are ranging from (5-81 years). The data collected include sex, gender, chief complaint, surgery, histopathology, site of malignancy, and treatment protocols. The results showed that males (60.87%) were more prevalent than females (39.13%). Approximately, group 41-60 years was the common group affected (39, 42.4%). Always, most patients complained of headache in 86(93.48%). The majority of cases underwent incisional biopsies (51, 55.44%). About 13(14.13%) of patients operated on seemly with gross total resection, whereas 28(30.43%) have a subtotal resection. Low-grade gliomas were common pathology in 25%, while high grade gliomas, i.e. GBM in 13% and anaplastic gliomas in 15.2%. We found meningioma in 15.2%. The parietal lobe was the common site occupied by gliomas in (38%). Surgery was the mainstay in this study, in addition to it, RT performed in 33.69%, CCRT in 26%, and CCRT plus maintenance MTZ in 24%. Otherwise, 15(16.31%) of cases were managed with radical RT. In conclusion, frequently male with middle age is more affected than female. Headache is a common alarm for CNS tumors in our country. High-grade and advanced gliomas are common in our nationality. Surgical resection followed by CCRT or RT is the better way to get a good outcome.